(untitled) (Research, Society and Development, 2022)
About one-quarter of the world’s population is infected by geohelminths. The aim of this research was investigated the prevalence and predictors associated with intestinal parasites in children on over two decades. A retrospective study was conducted with children (0-18 years old) attended in the period of 1997-2016 by a public institution in southern Brazil. Data analysis was carried out using Stata® 9.1. A total of 7,292 records were analyzed; the overall prevalence was 25.5%. Most records showed infection by protozoa (69.4%). The most prevalent intestinal parasites were Entamoeba coli (9.4%) and Giardia duodenalis (8.9%). Statistically significant (p<0.05) associations were found between intestinal parasites and predictor variables of sex and age. The highest infection rates were detected in subjects from 0-4 years old (y/o) by G. duodenalis (OR 7.2, p<0.001). The lowest infection rates were in the 10-14 y/o group (OR 1.7, p<0.001). In all age groups, G. duodenalis caused the most infections and was more common in males (OR 1.3; p<0.001). Our findings show consistent prevalence with important predictors. We also detected a downward trend in intestinal parasite prevalence in the 20 years of observance.